Neu Perspectives, Therapies, and Challenges for Metastatic HER2-Positive Breast Cancer - Salkeni MA (Dove Medical Press, 2021)
Mohamad Adham Salkeni,1 Wajeeha Rizvi,2 Kyaw Hein,3 Gerald M Higa4 1Division of Cancer Treatment and Diagnosis, National Cancer Institute, National Institutes of Health, Bethesda, MD, USA; 2Department of Internal Medicine, West Virginia University, Morgantown, WV, USA; 3Department of Business, Lamar University, Houston, TX, USA; 4Departments of Clinical Pharmacy and Medicine, West Virginia University, Morgantown, WV, USACorrespondence: Gerald M HigaDepartments of Clinical Pharmacy and Medicine, West Virginia University, Morgantown, WV, 26506, USAEmail ghiga@hsc.wvu.eduAbstract: Even though gene amplification or protein overexpression occurs in approximately one-fifth of all breast cancers, the discovery of HER2 has, nevertheless, had profound implications for the disease. Indeed, the characterization of the receptor resulted in a number of significant advances. Structurally, unique features provided avenues for the development of numerous compounds with target-specificity; molecularly, biological constructs revealed a highly complex, internal signal transduction pathway with regulatory effects on tumor proliferation, survival, and perhaps, even resistance; and clinically, disease outcomes manifested its predictive and prognostic value. Yet despite the receptor’s utility, the beneficial effects are diminished by tumor recurrence after neo- or adjuvant therapy as well as losses resulting from the inability to cure patients with metastatic disease. What these observations suggest is that while tumor response may be partially linked to uncoupling cell surface message reception and nuclear gene expression, as well as recruitment of the innate immune system, disease progression and/or resistance may involve a reprogrammable signaling mainframe that elicits alternative growth and survival signals. This review attempts to meld current perceptions related to HER2-positive metastatic breast cancer with particular attention to current biological insights and therapeutic challenges.Keywords: ado-trastuzumab emtansine, ErbB, Fam-trastuzumab deruxtecan, HER2, lapatinib, margetuximab, neratinib, neu, pertuzumab, PHESGO, trastuzumab, tucatinib